PELAKSANAAN STRATEGI COOPERATIVE LEARNING PADA PROSES PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN SIKAP NASIONALISME PESERTA DIDIK KELAS XI SMAN 16 PADANG - Nuri Qur’Ani; Buchari Nurdin; Ranti Nazmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Cooperative Learning strategy in Pancasila Education learning to improve the nationalism attitudes of eleventh-grade students at SMAN 16 Padang. The study employed a qualitative approach using a descriptive method. The research participants consisted of a Pancasila Education teacher and eleventh-grade students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the teacher systematically designed learning modules by integrating nationalism values into learning objectives, materials, instructional strategies, and assessment. The implementation of the Cooperative Learning strategy, combined with lectures, group discussions, question-and-answer sessions, and presentations, enhanced students' active participation while fostering discipline, responsibility, cooperation, national spirit, and love for the homeland. Assessment was conducted through cognitive, skills, and attitude evaluations, enabling continuous monitoring of students' nationalism development. Therefore, the Cooperative Learning strategy effectively supports active, collaborative, and student-centered learning in strengthening students' nationalism attitudes.